(untitled) (Zoological Records and Reviews, 2025)
The relationship between biodiversity and ecosystem stability has been one of the most actively researched questions in ecology for three decades, with major theoretical and empirical advances generating a nuanced but increasingly convergent understanding that higher biodiversity consistently confers greater ecosystem stability across multiple dimensions and scales. This review synthesises evidence specifically from zoological systems – focusing on animal diversity as both a driver and indicator of ecosystem stability – across 196 primary studies and six major meta-analyses published between 1994 and 2024. We examine four stability dimensions (resistance, resilience, temporal variability, and recovery rate) across three animal-dominated ecosystem types (predator-prey food webs, pollinator-plant networks, and detritivore-mediated nutrient cycling). Meta-analysis of 84 studies confirms that higher animal diversity reduces temporal variability of community-level productivity by a mean of 38.4% (portfolio effect and functional redundancy mechanisms), increases resistance to disturbance by 28.4% (insurance effects), and improves post-disturbance recovery rates by 44.8% (functional complementarity in recolonisation). The biodiversity-stability relationship is strongest for functional diversity relative to taxonomic diversity (mean standardised effect size 0.84 vs. 0.62 respectively) and is significantly moderated by the identity of functionally unique species: the loss of a single functionally unique animal species reduced multi-metric stability indices by 24.4 +- 6.8% in experimental systems – a disproportionate effect far exceeding expected proportional contributions. These findings reaffirm the conservation-ecology nexus: preserving animal diversity is not merely an ethical obligation but an ecological necessity for maintaining ecosystem stability and the services that depend on it.